Sosio-Kultural dalam Masyarakat Aceh: Strategi Perlindungan Hukum bagi Korban Kekerasan Dalam Rumah Tangga - Sahara, Siti; Natsir, Muhammad; Zuleha, Zuleha; Yusuf, Darmawi; Mansari, Mansari (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
This study examines the weaknesses in Law Number 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT), particularly concerning the absence of provisions for restitution for victims of domestic violence (KDRT). Restitution, as a form of financial compensation given by the perpetrator to the victim, is regulated in Aceh's Qanun Number 9 of 2008 on the Development of Acehnese Life, which reflects the socio-cultural practices of the Acehnese community in providing protection and recovery for KDRT victims. However, this provision is not included in the UU PKDRT, making it unenforceable by public prosecutors in the national legal context. This study employs an empirical legal research method with data collection techniques through interviews to gather perspectives from traditional leaders, Keuchik, Tuha Peut, Imeum Gampong, and other relevant parties regarding the application and shortcomings of the UU PKDRT. The absence of restitution provisions in the UU PKDRT is a significant weakness that hinders comprehensive protection for KDRT victims. The adoption of restitution provisions into national law through the UU PKDRT is highly feasible, considering that the purpose of the law is for humans and to realize the welfare of the entire society. This policy reformulation is expected to strengthen legal protection for KDRT victims and accommodate existing socio-cultural values in society. [Penelitian ini mengkaji kelemahan dalam Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga (UU PKDRT), khususnya terkait dengan tidak diaturnya restitusi bagi korban kekerasan dalam rumah tangga. Restitusi, sebagai bentuk kompensasi penggantian kerugian yang diberikan oleh pelaku kepada korban, telah diatur dalam Qanun Aceh Nomor 9 Tahun 2008 tentang Pembinaan Kehidupan Aceh, yang mencerminkan praktik sosio-kultural masyarakat Aceh dalam memberikan perlindungan dan pemulihan bagi korban KDRT. Namun, ketentuan ini tidak tercantum dalam UU PKDRT, sehingga tidak dapat dilaksanakan oleh penuntut umum dalam konteks hukum nasional. Penelitian ini menggunakan metode penelitian hukum empiris dengan teknik pengumpulan data melalui wawancara untuk mendapatkan pandangan dari para tokoh adat, Keuchik, Tuha Peut, dan Imeum Gampong serta pihak-pihak terkait mengenai penerapan dan kelemahan UU PKDRT. Ketiadaan pengaturan restitusi dalam UU PKDRT merupakan kelemahan signifikan yang menghambat perlindungan menyeluruh terhadap korban KDRT. Adopsi ketentuan restitusi ke dalam hukum nasional melalui UU PKDRT sangat mungkin dilakukan, mengingat tujuan hukum adalah untuk manusia dan untuk mewujudkan kemaslahatan bagi seluruh masyarakat. Reformulasi kebijakan ini diharapkan dapat memperkuat perlindungan hukum bagi korban KDRT dan mengakomodasi nilai-nilai sosio-kultural yang ada di masyarakat].